Preliminary evaluation of variability in Musa root system development - Blomme, Guy; Ortíz, R. (Springer, 1997)
Studies of Musa root systems have generally focused on the high value export dessert bananas. However, a much broader study is required to support the genetic improvement of plantains and cooking bananas. Detailed time course studies of root system development were carried out on 12 genotypes from six diverse Musa groups. The performance of tissue culture derived plants was compared with that of suckers taken from field grown plants. Genotypes were assessed during establishment of tissue culture plan-tlets in the nursery (at 2, 4 and 6 weeks old) and in the field (at 12 and 16 weeks old) (Table 1), and compared to the vegetative growth of suckers in the field (at 6, 8, 12 and 16 weeks). Tetraploid plantain hybrids (TMPx 1658-4, TMPx 548-9 and TMPx 5511-2) were compared with their maternal triploid plantain landrace genotypes (Obino l'Ewai) and their paternal diploid banana genotypes (Pisang Lilin and Calcutta 4). These were also compared with cooking banana cultivars (Cardaba and Fougamou), a cooking banana hybrid (FHIA3), dessert bananas (Valéry and Yangambi Km 5) and a plantain landrace (Ag- bagba). Significant correlations (p<0.05) across all genotypes were observed between above ground parameters and root parameters, irrespective of type of planting material or age (Table 2). Associations between leaf area, plant height, circumference at soil level and dry weight of the roots were significant over nearly all the age groups. There were no significant phenotypic correlations between root parameters of the two types of plant material at 6, 12 and 16 weeks old. This may suggest that different mechanisms affect root development, which may be controlled by different regulatory genetic systems, according to the type of propagule. The use of this type of data to formulate an ideotype, which will direct future breeding strategies at UTA, will be discussed.